A REVITALIZED ACCOUNTING CURRICULUM. - Wasley, Robert S. (The Accounting Review, 1963)
Abstract This article focuses on the accounting curriculum of the School of Business at the University of Colorado, Boulder, Colarado. The faculty of the School began to take a long, hard look at the curriculum which it was offering. Undoubtedily this has been done almost universally by the faculties of schools of business across the U.S. since the publication of these two studies. After long and careful study by the faculty of the School of Business at the University of Colorado, several basic changes have been instituted in the course of study. In order to appreciate the changes which have been made, it will first be necessary to explain the program as it stood originally. The School of Business is a two-year, upper-division school with students being required to take 60 semester hours of work outside of the School, and another 60 semester hours of work within the School in order to fulfill the requirements for graduation.